6‐hydroxydopamine‐induced Parkinson's disease‐like degeneration generates acute microgliosis and astrogliosis in the nigrostriatal system but no bioluminescence imaging‐detectable alteration in adult neurogenesis. (5th April 2016) - Fricke, Inga B.; Viel, Thomas; Worlitzer, Maik M.; Collmann, Franziska M.; Vrachimis, Alexis; Faust, Andreas; Wachsmuth, Lydia; Faber, Cornelius; Dollé, Frédéric; Kuhlmann, Michael T.; Schäfers, Klaus; Hermann, Sven; et al.
Abstract: Parkinson's disease is a slowly progressing neurodegenerative disorder caused by loss of dopaminergic neurons in the substantia nigra (SN), leading to severe impairment in motor and non‐motor functions. Endogenous subventricular zone (SVZ) neural stem cells constantly give birth to new cells that might serve as a possible source for regeneration in the adult brain. However, neurodegeneration is accompanied by neuroinflammation and dopamine depletion, potentially compromising regeneration. We therefore employed in vivo imaging methods to study striatal deafferentation ( N ‐ω‐fluoropropyl‐2β‐carbomethoxy‐3β‐(4‐[ 123 I]iodophenyl)nortropane single photon emission computed tomography, DaTscan ™ ) and neuroinflammation in the SN and striatum ( N, N ‐diethyl‐2‐(2‐(4‐(2‐[ 18 F]fluoroethoxy)phenyl)‐5, 7‐dimethylpyrazolo[1, 5‐a]pyrimidin‐3‐yl)acetamide positron emission tomography, [ 18 F]DPA‐714 PET) in the intranigral 6‐hydroxydopamine Parkinson's disease mouse model. Additionally, we transduced cells in the SVZ with a lentivirus encoding firefly luciferase and followed migration of progenitor cells in the SVZ–olfactory bulb axis via bioluminescence imaging under disease and control conditions. We found that activation of microglia in the SN is an acute process accompanying the degeneration of dopaminergic cell bodies in the SN. Dopaminergic deafferentation of the striatum does not influence the generation of doublecortin‐positive neuroblasts in the SVZ, but generates chronic astrogliosis in the nigrostriatal system. Abstract : Using multimodal in vivo imaging, we observed that activation of microglia is an acute process coming along with the 6‐hydroxydopamine‐induced degeneration of dopaminergic cell bodies in the substantia nigra. Dopaminergic deafferentation of the striatum has no influence on subventricular zone neuroblast generation and neural progenitor cell migration towards the olfactory bulb, but generates chronic astrogliosis in the nigrostriatal system.